Glucagon-like peptide 1 receptor agonists: A new approach to type 2 diabetes management - Lynn Lambert (South African Family Practice)
Despite advances in options for the treatment of type 2 diabetes, optimal glycaemic control is often not achieved. Hypoglycaemia and weight gain that are associated with many antidiabetic medications may interfere with the implementation and long-term application of treatment strategies. Glucose homeostasis is dependent on a complex interplay of multiple hormones and gastrointestinal peptides, including glucagon-like peptide 1 (GLP-1). Abnormal regulation of these substances may contribute to the clinical presentation of diabetes. GLP-1-based therapies affect glucose control without causing hypoglycaemia through several mechanisms, including enhancement of glucose-dependent insulin secretion, slowed gastric emptying, regulation of postprandial glucagon and reduction of food intake.